Modern Probabilistic Methods for Analysis of Telecommunication Networks Belarusian Winter Workshops in Queueing Theory, BWWQT 2013, Minsk, Belarus, January 28-31, 2013. Proceedings - Dudin, Alexander; Klimenok, Valentina; Tsarenkov, Gennadiy; Dudin, Sergey; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the refereed proceedings of the International Conference on Modern Probabilistic Methods for Analysis of Telecommunication Networks, Belarusian Winter Workshop in Queueing Theory, BWWQT 2013, held in Minsk, Belarus, in January 2013. The 23 revised full papers presented were carefully reviewed and selected from numerous submissions. The papers present new results in study and optimization of information transmission models in telecommunication networks using different approaches, mainly based on theories of queueing systems and queueing networks.
Keywords: Computer science; Computer communication systems; Computer system failures; Mathematical statistics; Computer Science; Probability and Statistics in Computer Science; Computer Communication Networks; System Performance and Evaluation; Electronic books